Meta-analysis of scientific data on GIFT: a contribution to ethical judgements
Meta-analysis is a new discipline that critically reviews the results of previous research, particularly in the field of clinical trials. The authors of this article put forward the hypothesis that modified meta-analysis of scientific data in GlFT procedures might be useful in deducing some ethical indications in this field. The analysis of the results of the GIFT procedure shows that there is a lower number of births than pregnancies begun, since some fetal losses occur during the pregnancics. The authors conclude that these fetal losses cannot be justified by ascertaining that "also in naturally started pregnancies similar fetal losses occur". Morcover the GIFT technique itself plays a decisive role in the loss of fetuses during the GIFT procedure. Even though meta-anal